NiZrSe3/rGO modulated porous architecture for hybrid featured asymmetric supercapacitors. (July 2023) - Aziz, Muhammad Hammad; Khan, Arif; Fahad, Hafiz Muhammad; Shaheen, Fozia; Ahmad, Riaz; Mehboob, Khurram; Huang, Qing
Abstract: Designing transition metallic chalcogenides with rGO as a potential porous platform for growth are vital to upsurge the electrochemical energy storage capabilities of supercapacitors' electrodes. This work reports hydrothermally prepared agglomerated NiZrSe3 nanoparticles and a porous NiZrSe3 /rGO, where the latter exhibits superior charge storage properties. In comparison to NiZrSe3 with specific capacitance ( C s ) of 1415.7 F/g, the porous modulated material NiZrSe3 /rGO delivers an exceptional C s of 2750.8 F/g at current density of 2 A/g in the 3-electrode setup. Due to its the outstanding electrochemical performance, NiZrSe3 /rGO is employed as a redox featured electrode material, and further integrated with activated carbon (ActC) as a capacitive featured electrode material to construct a hybrid asymmetric supercapacitor with widened potential window and enhanced energy density. The constructed asymmetric supercapacitor unveils a specific capacitance of 140.77 F/g at current density of 1.2 A/g and rate capability of 53.6 % at 7 A/g while functioning stably under the potential range of 0–1.65 V. Moreover, it achieves extremely high energy density of 53.22 Wh/kg at power density of 990 W/kg with its long-life span in regard to cyclic stability of 80.31 % after 10, 000 charging-discharging cycles. In general, this work illustrates the significance of NiZrSe3 /rGO as a highly redox active cathode material in hybrid featured asymmetric supercapacitors for future renewable energy storage systems. Graphical abstract: Unlabelled Image Highlights: NiZrSe3 /rGO composite was fabricated via hydrothermal method. The integration of rGO reduced the agglomeration of NiZrSe3 nanoparticles. b -Fit value of NiZrSe3 /rGO was 0.61, showing mixed charge storage mechanism. NiZrSe3 /rGO was employed as a faradic type electrode material for making hybrid asymmetric supercapacitors (ASC). NiZrSe3 /rGO||Act-C ASC achieved an extraordinary energy density of 53.22 Wh/kg at power density of 990 W/kg.